1999
DOI: 10.1023/a:1008377921886
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor measured in platelet poor plasma allows optimal separation between cancer patients and volunteers: A key to study an angiogenic marker in vivo?

Abstract: It is likely that VEGFS in cancer patients encompass platelet-delivered VEGF and VEGF from other sources, notably from (neo)-angiogenesis in tumoral tissue. The best discrimination between volunteers and cancer patients was observed in PPP. As generating plasma can induce platelet activation, with consequent VEGF release from platelets, we suggest that to assess free circulating VEGF, CTAD plasma should be used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
67
0
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 32 publications
3
67
0
2
Order By: Relevance
“…This ratio gives a rough estimation of how much VEGF is contained in the platelets 23,24 and we found that platelets of MMM patients contained four times more VEGF than those of healthy controls: median 0.99 pg per 10 6 platelets (range 0.6-3.1) vs 0.25 pg per 10 6 platelets (range 0.09-0.8) for MMM patients and controls respectively (Figure 2). Taken together, these data indicate that platelets may be a major source of VEGF both in MMM patients and in normal subjects and that platelets from patients contain a higher amount of VEGF.…”
Section: Resultsmentioning
confidence: 89%
“…This ratio gives a rough estimation of how much VEGF is contained in the platelets 23,24 and we found that platelets of MMM patients contained four times more VEGF than those of healthy controls: median 0.99 pg per 10 6 platelets (range 0.6-3.1) vs 0.25 pg per 10 6 platelets (range 0.09-0.8) for MMM patients and controls respectively (Figure 2). Taken together, these data indicate that platelets may be a major source of VEGF both in MMM patients and in normal subjects and that platelets from patients contain a higher amount of VEGF.…”
Section: Resultsmentioning
confidence: 89%
“…The strong correlation between serum and plasma VEGF may reflect the fact that plasma VEGF levels are directly related to total blood VEGF levels and correspond to free VEGF after equilibration with platelet levels (George et al, 2000). Alternatively, we cannot rule out that the platelet VEGF released following a partial platelet degradation during plasma sampling and storage, may account for part of the EDTA plasma VEGF (Wynendaele et al, 1999).…”
Section: Prognostic Value Of Angiogenic Factors In Breast Cancer T Bamentioning
confidence: 99%
“…These levels have been correlated to the clinical course of the disease in several tumour types (Poon et al, 2001;Ugurel et al, 2001;Molica et al, 2002). As most serum VEGF is released from platelets during blood clotting, it has been suggested that plasma VEGF may be a better reflection of ongoing angiogenic activity, although this assumption has been challenged (Banks et al, 1998;Salven et al, 1999a;Wynendaele et al, 1999;George et al, 2000). To date, plasma VEGF has not been shown to be a better prognostic factor than serum VEGF in any solid tumour (Werther et al, 2002).…”
mentioning
confidence: 99%
“…CTAD tubes contained sodium citrate, theophyllin, adenosine and dipyridamine allowing maximal platelet stabilization. The tubes were centrifuged within 15 min at 2500!g for 30 min at 4 8C [31]. The resulting plasma was separated and stored immediately at K80 8C.…”
Section: Blood Samples and Vegf Assaymentioning
confidence: 99%
“…The resulting plasma was separated and stored immediately at K80 8C. The technique of blood sampling and handling of probes has been published previously [10,31]. Thrombocyte count in CTAD plasma was measured and the amount was at the detection limit (!5000).…”
Section: Blood Samples and Vegf Assaymentioning
confidence: 99%